2017
DOI: 10.7150/jca.19364
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of ABC Transporters in Non-neoplastic Tissues Confers Better Prognosis for Pancreatic and Colorectal Cancer Patients

Abstract: Transport of a wide variety of substrates, including xenobiotics, is one of the main functions attributed to human ATP-binding cassette (ABC) proteins. Overexpression of ABC genes is considered to be an important mechanism facilitating the development of chemoresistance. Relationships between the expression levels of ABC genes in tumor tissues and established clinicopathological features were extensively studied previously. The current study tested our hypothesis that the expression levels of ABC genes in non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Eight ABC transporter subfamilies have been identified based on transporter homology and structural similarity [27]. A study suggested that downregulation of ABC transporters in nonneoplastic tissues may be associated with better prognoses for pancreatic cancer and colorectal cancer [28]. The common DEGs identified in our study were shown to be significantly involved in cancer-related functions and signaling pathways.…”
Section: Discussionmentioning
confidence: 59%
“…Eight ABC transporter subfamilies have been identified based on transporter homology and structural similarity [27]. A study suggested that downregulation of ABC transporters in nonneoplastic tissues may be associated with better prognoses for pancreatic cancer and colorectal cancer [28]. The common DEGs identified in our study were shown to be significantly involved in cancer-related functions and signaling pathways.…”
Section: Discussionmentioning
confidence: 59%
“…Biology 2020, 9, x FOR PEER REVIEW 4 of 38 the prognosis of colon cancer patients receiving 5-FU treatment with studies reporting both negative and positive correlations [20][21][22][23]. Nonetheless, incidence of 5-FU resistance is still consistently motivated by elevated levels of ABC transporters, that includes ABCB1 [P-glycoprotein (P-gp) or MDR1] [24,25]; ABCG2 [breast cancer resistance protein (BCRP)] [26,27]; ABCC1 [multidrug resistance-associated protein (MRP1)] [28,29]; ABCC3 [20], and ABCC2 [30].…”
Section: Alterations In Drug Transportsmentioning
confidence: 99%
“…Following the analysis of 27 non-neoplastic pancreatic tissues and pairing them with 32 PDAC samples, 4 different clusters could be distinguished based on the gene expression profiles in cancer vs normal specimens. PN1 and PN2 clusters were characterized by upregulation of the majority of ABC transporters genes and correlated with significantly shorter patients’ overall survival (OS) than patients grouped into PN3 and PN4 clusters, in which significant downregulation of genes or heterogeneous gene expression has been observed[ 119 ]. Especially, ABCA2, ABCA4, ABCA5, ABCC2 and ABCD4 signatures showed significant difference in patients’ survival when comparison between upregulated and downregulated genes was carried out.…”
Section: Abc Transporters Expression Profiles As Prognostic Markers Imentioning
confidence: 99%